Essential Elements of Multimodal Analgesia in Enhanced Recovery After Surgery (ERAS) Guidelines - Beverly, Anair; Kaye, Alan D; Ljungqvist, Olle; Urman, Richard D (Anesthesiology clinics, 2017)
Perioperative multimodal analgesia uses combinations of analgesic medications that act on different sites and pathways in an additive or synergistic manner to achieve pain relief with minimal or no opiate consumption. Although all medications have side effects, opiates have particularly concerning, multisystemic, long-term, and short-term side effects, which increase morbidity and prolong admissions. Enhanced recovery is a systematic process addressing each aspect affecting recovery. This article outlines the evidence base forming the current multimodal analgesia recommendations made by the Enhanced Recovery After Surgery Society (ERAS). We describe current evidence and important future directions for effective perioperative multimodal analgesia in enhanced recovery pathways.